2006
DOI: 10.1016/s1472-6483(10)61191-1
|View full text |Cite
|
Sign up to set email alerts
|

How to improve IVF–ICSI outcome by sperm selection

Abstract: In previous studies, a new IVF method of intracytoplasmic morphologically selected sperm injection (IMSI) was introduced, based on motile sperm organellar morphology examination (MSOME). It was concluded that microinjection of morphologically selected sperm cells with strictly normal nucleus, defined by MSOME, improves IVF-ICSI outcome. The aim of the present study was to confirm this conclusion in new, enlarged study groups. Comparison between 80 couples, who underwent an IVF-IMSI trial, with matched couples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
114
1
11

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(135 citation statements)
references
References 18 publications
7
114
1
11
Order By: Relevance
“…This point implies the need for the employment of a higher optical magnification for sperm selection, especially for ICSI. Such a new proposal is important and could be implemented not only in couples with previous ICSI failures, as performed by Bartoov's methodology [26], but in general use for each routine ICSI procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This point implies the need for the employment of a higher optical magnification for sperm selection, especially for ICSI. Such a new proposal is important and could be implemented not only in couples with previous ICSI failures, as performed by Bartoov's methodology [26], but in general use for each routine ICSI procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Young women, of an average age of 24 (range [20][21][22][23][24][25][26], were accepted into the Egg Donation Program (EDP) cycles. All of these women were healthy, had normal menstrual cycles and no determined pathology.…”
Section: Oocytes Donation and Fertilizationmentioning
confidence: 99%
“…During ART procedures, semen is traditionally processed with the density gradient centrifugation or swim‐up techniques 5, 6. With ICSI, individual sperm are then selected visually based on motility and morphology by a trained embryologist for injection to an egg 7, 8. However, other important sperm attributes that can affect ART outcomes, including sperm DNA–chromatin or chromosomal integrity, mutational, or methylome composition, and the presence of reactive oxygen species (ROS)9, 10, 11, 12, 13, 14, 15, 16, 17 are typically not considered.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the negative impact of large nuclear vacuoles (LNV) is perceptible after the onset of the EGA, leading to reduced blastocyst formation [28][29][30][31]. Moreover, LNV also affect ongoing pregnancy rates [31][32][33][34], miscarriage rates [31,33,[35][36][37], and malformation in offspring [38,39].…”
Section: Introductionmentioning
confidence: 99%